Study of histological changes of uterus in perimenopausal women with abnormal uterine bleeding - Nabanita Chakraborty; Kundu Banani; Nandini Goswami; Soham Chakraborty (Al Ameen Medical College, 2022)
Background: Abnormal uterine bleeding (AUB) is a very common problem found in perimenopausal women and also the most common cause of gynecological visit and hysterectomy. Perimenopause is the interval in which a woman's body makes a natural shift from regular cycles of ovulation and menstruation to irregular cycles. Leiomyoma, Dysfunctional Uterine Bleeding and Adenomyosis are most frequently encountered benign causes of AUB in this age group. The histological diagnosis of these diseases is very essential for management and also to differentiate them from the malignancy and hyperplasia - the other common causes of AUB. Aims and Objectives: Primary aim of our study was to identify the spectrum of histological changes that occur in the endometrium in perimenopausal age group and to identify the demographic pattern of each histological changes. Materials and Methods: Fifty nine specimens of hysterectomy obtained from the patients of the perimenopausal age group of 40-50 years attending the Gynaecology and Obstetrics department were studied. Following hysterectomy, the specimen were collected and prepared through multistep processes. Finally they were stained by Hematoxylin-Eosin and viewed under microscope. The results were tabulated and photomicrographs of the histological slides were obtained. Results: Mostly Leiomyoma (30.51%) followed by Dysfunctional Uterine Bleeding (20.34%) and Adenomyosis (15.25%) were diagnosed among the fifty nine cases of hysterectomy patients in perimenopausal age group and proliferative endometrium (42.37%) is the most common histological finding. Conclusion: AUB in perimenopausal age group is common but ill-defined entity. It reflects a spectrum of endometrial histology. This study has also highlighted the correlation of endometrial histology with final diagnosis of patients. This may help to establish early and appropriate management and minimize the patients sufferings.